Some problems in estimation of the optimum exploitation life of bucket wheel excavators - R. Zivojinovic; S. Vujic (The Southern African Institute of Mining and Metallurgy, 2003)
The structural age of the capital mining machinery, representing a part of the system of the Electric Power Industry of Serbia, has been dictated by the initiation and development of open pit coal mines. For example, the oldest bucket wheel excavators were installed some thirty-four years ago, and the average life of the relevant machinery exceeds twenty-two years. Operation of both capital equipment and machinery has direct effects on economic and business activities of open pit mines, and consequently forced us to make a decision and study thoroughly the problem of establishing the optimum exploitation life of capital mining equipment at the open pit coal mines of the Electric Power Industry of Serbia. The aim of this paper is to define and discuss the relative problems as well as to find out the possible solutions and establish the methodology for estimating the optimum exploitation life of machinery. The study was successfully carried out by a team of scientists engaged from and coordinated by the Department of Computer Science of the Faculty of Mining and Geology, University of Belgrade. This paper presents the key observations covering the subject problem. Keywords: Mining, Opencast exploitation, Coal, Optimization, Exploitation life, Capital machinery, Electric power industry, Dynamic programming.